Coccolithophore biodiversity controls carbonate export in the Southern Ocean - Rigual Hernández, Andrés Salvador; Trull, Thomas W.; Nodder, Scott D.; Flores Villarejo, José Abel; Bostock, Helen; Abrantes, Fátima; Eriksen, Ruth S.; Sierro Sánchez, Francisco Javier; Davies, Diana M.; Ballegeer, Anne-Marie Clara; Fuertes Prieto, Miguel Ángel; Northcote, Lisa C. (Biogeosciences, 2020)
[EN]Southern Ocean waters are projected to undergo profound changes in their physical and chemical properties in the coming decades. Coccolithophore blooms in the Southern Ocean are thought to account for a major fraction of the global marine calcium carbonate (CaCO3) production and export to the deep sea. Therefore, changes in the composition and abundance of Southern Ocean coccolithophore populations are likely to alter the marine carbon cycle, with feedbacks to the rate of global climate change. However, the contribution of coccolithophores to CaCO3 export in the Southern Ocean is uncertain, particularly in the circumpolar subantarctic zone that represents about half of the areal extent of the Southern Ocean and where coccolithophores are most abundant. Here, we present measurements of annual CaCO3 flux and quantitatively partition them amongst coccolithophore species and heterotrophic calcifiers at two sites representative of a large portion of the subantarctic zone. We find that coccolithophores account for a major fraction of the annual CaCO3 export, with the highest contributions in waters with low algal biomass accumulations. Notably, our analysis reveals that although Emiliania huxleyi is an important vector for CaCO3 export to the deep sea, less abundant but larger species account for most of the annual coccolithophore CaCO3 flux. This observation contrasts with the generally accepted notion that high particulate inorganic carbon accumulations during the austral summer in the subantarctic Southern Ocean are mainly caused by E. huxleyi blooms. It appears likely that the climate-induced migration of oceanic fronts will initially result in the poleward expansion of large coccolithophore species increasing CaCO3 production. However, subantarctic coccolithophore populations will eventually diminish as acidification overwhelms those changes. Overall, our analysis emphasizes the need for species-centred studies to improve our ability to project future changes in phytoplankton communities and their influence on marine biogeochemical cycles. European Union's Horizon 2020, Marie Skłodowska-Curie Individual fellowship